(untitled) (European Journal of Behavioral Sciences, 2020)
Oman has long lasting peaceful relations with its neighbours and the world. It is a small size Arabian Gulf state with very rich natural resources. Relations between Oman and Turkey was very pleasant in 15-19th centuries. A century of interrupted relations has started to resurrect in the recent years with the new economic, political treaties and socio-cultural relations between two nations. Turkey and its policies, TV serials, and political leaders are very well known in Oman, whereas Oman is not very familiar to the Turkish people. In this research, to understand the level of Oman’s image in Turkey, a survey was orchestrated on more than 500 respondents and striking findings demonstrate that Oman is not well-known well in Turkey. The survey was conducted physically in the shopping malls in Istanbul and virtually via online questionnaire. Social representation of the survey overlaps on the Turkish social facts. In comparison with Europeans and Asians, the Turkish public knows Oman more than double of the world public opinion. For example, the location of Oman is known 51.9% in Turkey, but 38.2% in the world; the existence of general elections in Oman is known in Turkey on the level of 32.7%, whereas in Europe 16.3%. This study, as a primary resource, shares and interprets the result of conducted survey and then suggests some policy alternatives to Oman to be known better in Turkey and the world as a public diplomacy tool.